Investigating ligands of cardiac Myosin-Binding Protein C (cMyBPC) as potential regulators of contractility and modifiers of hypertrophy. - Swanepoel, C. C. A. (Stellenbosch : Stellenbosch University, 2011)
Thesis (PhD ) -- Stellenbosch University, 2011.